Redes comunicacionais na gastronomia: os processos criativos dos chefs de cozinha - Lunardelli, Tatiana (2017)
Between 1 984 and 2011 Catalan chef Ferran Adrià produced something around 1 0,000 documents, including sketches, texts and photos of everything that was produced in El Bulli. Since the the grand opening of the restaurant Epice in São Paulo, led by Chef Alberto Landgraf, all the dishes development, from techniques, suppliers, researches, were recorded in a notebook and posted on the Instagram app. Many other chefs record their processes and eventually post them on Instagram. All these documents are slowly being shown in specialized publications and social networks. Can the reading of these notebooks, with the revelation of all the layers of research involved in the elaboration of a dish and the critical approach of the creative process, offer new elements to the journalists, a more technical look, free from only the personal judgment that floods today’s specialized press? The purpose of this research is to investigate the communicative relation in the creative process of chefs, focusing on the work of Catalan chef Ferran Adrià and chef Alberto Landgraf and also on other chefs that adopted the same type of creative processes recording. The research proposes an understanding of creative processes, that is, how this creation takes place, from the concept of creation as a network under construction, as is presented by Cecília Salles, which has as its theoretical foundation Peircean semiotic line, the network concept of Pierre Musso, in dialogue with thinkers of culture, like Edgar Morim and Iuri Lotman. The research also intends to establish interactions with gastronomy scholars such as Massimo Montanari and Carlos Alberto Dória. As for its methodology, a four-month follow-up of chefAlberto Landgraf's process was carried out and an analysis of the documents will be made, that is, the notebooks and annotations used by the chef in his creative process; analysis of the records made by the Catalan chef during the years of existence of his restaurant El Bulli, as well as documents posted on Instagram by other chefs and interviews conducted by me during the masters degree